Pemikiran Cinta Ibn Miskawayh - Anisa Rizkia Rahayu (Himpunan Peminat Ilmu-Ilmu Ushuluddin (HIPIUS), 2017)
This research aims to analyze Ibn Miskawayh’s thought of love in his book, Tah̩dzīb al-Akhlāq wa Tat̩hir al-‘Arāq (1938, published in Beirut). The explanations relate to Ibn Miskawayh’s thought of love in Islamic philosophy, love as part of virtue in social intercourse. His view about the definition of love, parts of love, ethics of friendship, and love as source of good deeds insocial implication ofreligious of worship.